Interpolation of Gentle Spaces - Mourad Ben Slimane; Hnia Ben Braiek (Abstract and Applied Analysis)
The notion of gentle spaces, introduced by Jaffard, describes what would be an “ideal” function space to work with wavelet coefficients. It is based mainly on the separability, the existence of bases, the homogeneity, and the γ-stability. We prove that real and complex interpolation spaces between two gentle spaces are also gentle. This shows the relevance and the stability of this notion. We deduce that Lorentz spaces Lp,q and Hp,q spaces are gentle. Further, an application to nonlinear approximation is presented.